Dinosaurs - Osborne, Will.; Osborne, Mary Pope.; Murdocca, Sal (New York : Random House, 2000)
Jack and Annie explain about all the different types of dinosaurs.
"A Stepping Stone book."
Keywords: Dinosaurs